2021
DOI: 10.3389/fncel.2021.695380
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Ca2+ Signaling in Epilepsy

Abstract: Epilepsy is one of the most common neurological disorders – estimated to affect at least 65 million worldwide. Most of the epilepsy research has so far focused on how to dampen neuronal discharges and to explain how changes in intrinsic neuronal activity or network function cause seizures. As a result, pharmacological therapy has largely been limited to symptomatic treatment targeted at neurons. Given the expanding spectrum of functions ascribed to the non-neuronal constituents of the brain, in both physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 116 publications
0
10
0
Order By: Relevance
“…We hypothesized that such long‐lasting depressed state might be due to recruitment of astroglial networks that are shown to be important for clearing excess glutamate. 15 , 25 , 37 To test this hypothesis, we measured the astroglial calcium signals during photic stimulation. Astroglial calcium signals displayed strikingly different photic responses (Figure 6B ) when compared to the neurons (Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that such long‐lasting depressed state might be due to recruitment of astroglial networks that are shown to be important for clearing excess glutamate. 15 , 25 , 37 To test this hypothesis, we measured the astroglial calcium signals during photic stimulation. Astroglial calcium signals displayed strikingly different photic responses (Figure 6B ) when compared to the neurons (Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that this hyperexcitable elevated state is often followed by a slow and long‐lasting depressed state, which is particularly prominent in the PTZ model. We hypothesized that such long‐lasting depressed state might be due to recruitment of astroglial networks that are shown to be important for clearing excess glutamate 15,25,37 . To test this hypothesis, we measured the astroglial calcium signals during photic stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the effect of calcium modulation, the results of inhibition experiments with cilnidipine showed dose-dependent decrease in astrocyte oscillations, and it was consistent with those reported by Fleischer et al ( Figure 3C ). In addition, many previous studies reported that intracellular Ca 2+ concentration in astrocytes dynamically changed in response to drugs ( Heuser and Enger, 2021 ). Therefore, changes in calcium concentration have a role in astrocyte oscillations observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy not only results from overexcitation of neurons but also is a condition in which excitation occurs repeatedly. Thus, in addition to the clarification of ictogenesis and neuronal overexcitation, the mechanism by which epileptic seizures are repeated needs to be elucidated, or in other words, the mechanism that makes epilepsy more likely to occur needs to be determined [ 19 , 20 ]. This situation, in which the brain becomes prone to recurrent epileptic seizures is called epileptogenesis.…”
Section: Epileptogenesis and Aberrant Ca 2+ Signals In Epileptogenic Astrocytesmentioning
confidence: 99%
“…In this review, we will focus on aberrant Ca 2+ signals as a phenotype of reactive astrocytes. We show some examples of brain dysfunctions such as neuropathic pains [ 11 , 12 , 17 , 18 ], epileptogenesis [ 19 , 20 , 21 ], and Alexander disease (AxD) [ 22 ], where aberrant Ca 2+ signals in astrocytes are commonly observed and are highly involved in the cause of these pathogenesis.…”
Section: Introductionmentioning
confidence: 99%